Preferences for induction of labor methods in India: a qualitative study of views and experiences of women, clinicians, and researchersAJOG Global Reports at a Glance - Lydia A. Hawker, MBChB; Shuchita Mundle, MD; Jaya P. Tripathy, MD; Pradeep Deshmukh, MD; Beverly Winikoff, MD; Andrew D. Weeks, MD; Carol Kingdon, PhD; Kate Lightly, PhD (AJOG Global Reports)
Background: Induction of labor (IOL) is an increasingly common intervention, but experiences and preferences of induction methods are under-researched particularly in low -and middle-income countries. Understanding these perspectives is important to improve the childbirth experience. Objective: To explore the experiences and preferences of IOL methods for women, clinicians, and researchers in the “Misoprostol or Oxytocin for Labour Induction” (MOLI) study. Study Design: This qualitative study was based in two government hospitals in the city of Nagpur, India—one tertiary referral hospital and one women's hospital. Fifty-three semi-structured interviews with women before and after induction (between days 1 and 5 postnatal), with women recruited to the “Misoprostol or Oxytocin for Labour Induction (MOLI)” randomized controlled trial (NCT03749902). Eight focus group discussions with doctors, nurses, and trial research assistants before and during trial delivery were conducted. Thematic analysis was conducted using the Framework approach. Results: Four themes emerged: (1) IOL methods, (2) impact of the study, (3) IOL and childbirth as one small part of the wider experiences in life, and (4) key moments in the childbirth experience. For women, the safety of their baby was more important than any IOL method. Clinicians had apprehensions over misoprostol use which could affect protocol implementation; they reported that changing perception is difficult as usual practice feels “comfortable.” Women wanted to share their experiences and reported key moments during childbirth including vaginal examinations, “trying for normal,” bearing the pain, waiting, and relationships with staff. Conclusion: Women did not have a strong preference for the IOL method and viewed childbirth positively when maternal and neonatal outcomes were good. Labor pain, vaginal examinations, a normal birth, and interactions with staff impacted women's experiences.